Gas-Stabilizing Sub-100 nm Mesoporous Silica Nanoparticles for Ultrasound Theranostics - Montoya Mira, Jose; Wu, Lucy; Sabuncu, Sinan; Sapre, Ajay; Civitci, Fehmi; Ibsen, Stuart; Esener, Sadik; Yildirim, Adem (ACS omega, 2020)
Recent studies have demonstrated that gas-stabilizing particles can generate cavitating micron-sized bubbles when exposed to ultrasound, offering excellent application potential, including ultrasound imaging, drug delivery, and tumor ablation. However, the majority of the reported gas-stabilizing particles are relatively large (>200 nm), and smaller particles require high acoustic pressures to promote cavitation. Here, this paper reports the preparation of sub-100 nm gas-stabilizing nanoparticles (GSNs) that can initiate cavitation at low acoustic intensities, which can be delivered using a conventional medical ultrasound imaging system. The highly echogenic GSNs (F127-hMSN) were prepared by carefully engineering the surfaces of ∼50 nm mesoporous silica nanoparticles. It was demonstrated that the F127-hMSNs could be continuously imaged with ultrasound in buffer or biological solutions or agarose phantoms for up to 20 min. Also, the F127-hMSN can be stored in phosphate-buffered saline for at least a month with no loss in ultrasound responsiveness. The particles significantly degraded when diluted in simulated body fluids, indicating possible biodegradation of the F127-hMSNs in vivo. Furthermore, at ultrasound imaging conditions, F127-hMSNs did not cause detectable cell death, supporting the potential safety of these particles. Finally, strong cavitation activity generation by the F127-hMSNs under high-intensity focused ultrasound insonation was demonstrated and applied to effectively ablate cancer cells.